Extracellular vesicles from adipose stromal cells combined with a thermoresponsive hydrogel prevent esophageal stricture after extensive endoscopic submucosal dissection in a porcine model. Issue 35 (1st September 2021) - Coffin, Elise; Grangier, Alice; Perrod, Guillaume; Piffoux, Max; Marangon, Iris; Boucenna, Imane; Berger, Arthur; M'Harzi, Leila; Assouline, Jessica; Lecomte, Thierry; Chipont, Anna; Guérin, Coralie; et al.
Abstract : We show herein that a combination of a biomaterial and extracellular vesicles (produced at a high yield by a turbulence stimulation from stromal cells) was effective in the prevention of esophageal stricture in a clinically relevant porcine model. Abstract : In this study, we investigated the combination of extracellular (nano) vesicles (EVs) from pig adipose tissue-derived stromal cells (ADSCs) and a thermoresponsive gel, Pluronic® F-127 (PF-127), to prevent stricture formation after endoscopic resection in a porcine model. ADSC EVs were produced at a liter scale by a high-yielding turbulence approach from ADSCs 3D cultured in bioreactors and characterized in terms of size, morphology and membrane markers. The thermoresponsive property of the PF-127 gel was assessed by rheology. The pro-regenerative potency of ADSC EVs was investigated ex vivo in esophageal biopsies under starvation. In vivo tests were performed in a porcine model after extended esophageal endoscopic mucosal dissection (ESD). Pigs were randomized into 3 groups: control ( n = 6), gel ( n = 6) or a combination of 1.45 × 10 12 EVs + gel ( n = 6). Application of gel ± EVs was performed just after ESD with a follow-up finalized on day 21 post-ESD. There was a trend towards less feeding disorder in the EV + gel group in comparison with the gel and the control groups (16.67% vs. 66.7% vs. 83.33%, respectively) but without reaching a statistically significant difference. A significant decrease in the esophageal stricture rate was confirmed by endoscopic, radiological and histological examination for the EV + gel group. A decrease in the mean fibrosis area and larger regenerated muscularis mucosae were observed for the EV + gel group. In summary, the application of EVs + gel after extended esophageal endoscopic resection succeeded in preventing stricture formation with an anti-fibrotic effect. This nano-therapy may be of interest to tackle an unmet medical need considering that esophageal stricture is the most challenging delayed complication after extended superficial cancer resection by endoscopy.